Sugar production from durian (Durio zibethinus Murray) peel by acid hydrolysis - None Matura; None Woatthichai; Naranong Nuanphan (My University, 2013)
Agricultural waste is mainly composed of cellulose and hemicelluloses which can be converted to sugars. The inexpensive sugar from durian peel was hydrolyzed with H2SO4, HCl and H3PO4 at a concentration of 0.5 to 2.0% (v/v). The hydrolysis times ranging from 15 to 60 min were investigated when the mixture was autoclaved at 121°C. The result shows that acid hydrolysis efficiency (AHE) with H2SO4, HCl and H3PO4 had values of 72.15 to 77.55, 70.78 to 80.99 and 73.33 to 77.34%, respectively. Hydrolysis with H2SO4 and HCl led to increased concentration of AHE, reducing sugar and total sugar, while hydrolysis with H3PO4 had no effect on all values. Hydrolysis time had no effect on AHE, reducing sugar and total sugar in hydrolysis with H2SO4 and HCl; while in hydrolysis with H3PO4, the increasing time increased AHE and reducing sugar but had no effect on total sugar. Sugar in the hydrolysates was determined by high performance liquid chromatography (HPLC). In hydrolysis with H2SO4 and HCl, glucose, fructose and xylose were found while in hydrolysis with H3PO4, glucose and fructose were found. Key words: Acid hydrolysis efficiency (AHE), hydrolysis, durian peel, reducing sugar, total sugar.
Keywords: Reducing sugar; Biofuel production and bioconversion